(untitled) (Pedagogy of Higher and Secondary Education, 2012)
Palamar S. P. Formulation of subject competencies of primary school students in the process of vivchenny disciplines of the humanities cycle. In the article the way of formation of subject competence of pupils in primary schools studying Ukrainian literature, local history and literature at home reading. Justified by the language and literary options for working with literary texts.